Considering Bali's Agricultural Policies in Implementing the Development of MDA-Path Analysis - Rejeki, Sasi Wilujeng Sri; Solimun, Solimun; Nurjannah; Fernandes, Adji Achmad Rinaldo (JSMARTech, 2025)
The agricultural sector plays a vital role in Bali’s economy, culture, and food security, particularly in rice production. However, challenges such as land conversion and fluctuating farmer incomes have led the Bali government to implement various agricultural policies. Farmers' welfare is a critical factor in ensuring national food security, as prosperous farmers can improve production and maintain food stability. This study employs Discourse Network Analysis (DNA) to identify key factors affecting farmers' welfare in Bali and integrates MDA-Path Analysis to examine the relationships between exogenous variables and farmers' economic conditions. A mixed-method approach (qualitative and quantitative) is used to explore farmers' inclusivity and validate the MDA-Path Analysis model. Data is collected through in-sample validation using surveys conducted among farmers who are members of farmer groups in Bali. The results of this study indicate that human resource quality has the most significant impact on farmers' welfare, followed by price volatility and ease of technology use. The MDA-Path Analysis model demonstrates high classification accuracy, as reflected in sensitivity values exceeding 80%, confirming its effectiveness in distinguishing between different income and welfare categories. These findings provide valuable insights for strategic policy-making, enabling data-driven decision-making to enhance farmers' welfare and economic stability in Bali.